Analysis of Mathematics Teaching Efficacy Belief of Prospective Mathematics Teachers - Saija, Louise M; Hutajulu, Masta (IKIP Siliwangi, 2025)
Mathematics is a fundamental subject that plays a crucial role in students’ academic development, thus requiring competent teachers to effectively deliver mathematical concepts. One factor influencing teacher competence is mathematics teaching efficacy belief, which reflects a teacher’s confidence in their ability to teach mathematics successfully. This study aims to describe the mathematics teaching efficacy beliefs, among prospective mathematics teachers in West Java, Indonesia. The research involved 55 undergraduate students majoring in mathematics education from various universities in West Java. The instrument used to collect data was the Mathematics Teaching Efficacy Belief Instrument (MTEBI), originally developed by (Enochs et al., 2000) and translated into the Indonesian language. The MTEBI consists of two sub scales: Personal Mathematics Teaching Efficacy (PMTE) and Mathematics Teaching Outcome Expectancy (MTOE). Descriptive quantitative analysis was conducted to categorize students' efficacy beliefs. The results show that, on average, prospective mathematics teachers in West Java exhibit a high level of mathematics teaching efficacy belief. Most of them fall into the high category for PMTE, with none categorized as low. Additionally, nearly all participants scored high in MTOE, with mean scores higher than those in the PMTE dimension. These findings suggest that prospective mathematics teachers generally possess strong confidence in their teaching abilities and believe in the positive outcomes of their teaching efforts. This highlights the potential readiness of these future educators to effectively teach mathematics.